Age-related variation in health status after age 60. - Giola Santoni; Sara Angleman; Anna-Karin Welmer; Francesca Mangialasche; Alessandra Marengoni; Laura Fratiglioni (PLoS ONE)
Background Disability, functionality, and morbidity are often used to describe the health of the elderly. Although particularly important when planning health and social services, knowledge about their distribution and aggregation at different ages is limited. We aim to characterize the variation of health status in a 60+ old population using five indicators of health separately and in combination. Methods 3080 adults 60+ living in Sweden between 2001 and 2004 and participating at the SNAC-K population-based cohort study. Health indicators: number of chronic diseases, gait speed, Mini Mental State Examination (MMSE), disability in instrumental-activities of daily living (I-ADL), and in personal-ADL (P-ADL). Results Probability of multimorbidity and probability of slow gait speed were already above 60% and 20% among sexagenarians. Median MMSE and median I-ADL showed good performance range until age 84; median P-ADL was close to zero up to age 90. Thirty% of sexagenarians and 11% of septuagenarians had no morbidity and no impairment, 92% and 80% of them had no disability. Twenty-eight% of octogenarians had multimorbidity but only 27% had some I-ADL disability. Among nonagenarians, 13% had severe disability and impaired functioning while 12% had multimorbidity and slow gait speed. Conclusions Age 80-85 is a transitional period when major health changes take place. Until age 80, most people do not have functional impairment or disability, despite the presence of chronic disorders. Disability becomes common only after age 90. This implies an increasing need of medical care after age 70, whereas social care, including institutionalization, becomes a necessity only in nonagenarians.